Perubahan dan Strategi Adaptasi Organisasi dalam Mengatasi Tantangan dan Resistensi Internal - Cherli Aftariani; Dwi Pramana Putra; Alvit Alvit; Akdila Bulanov (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Organizational change is a necessity for every organization to maintain its existence and improve its effectiveness amid the rapid development of globalization and advances in information technology. Such changes often give rise to various challenges and internal resistance, whether stemming from organizational culture, functional differences, or the attitudes of organizational members toward change. This study aims to examine organizational change and adaptation strategies that can be applied to address internal challenges and resistance, enabling organizations to adapt effectively to environmental changes. The research method employed is a literature review (library research) using a traditional review approach. Data were obtained from various literature sources, such as scientific journals, books, and previous research relevant to the topics of organizational change and adaptation strategies. Analysis was conducted narratively and systematically to gain a comprehensive understanding of the concept of organizational change and its management strategies. Research findings indicate that organizational change requires systematic steps, ranging from assessment, identification, and definition of change, to strategy development and evaluation. Internal resistance is influenced by differences in functional orientation, organizational culture, and low member trust in the change. Effective adaptation strategies include the application of Lewin’s model, Kotter’s model, a participatory approach, open communication, resistance management, and continuous evaluation. In conclusion, the success of organizational change is largely determined by the organization’s ability to implement appropriate adaptation strategies, establish effective communication, and involve all members of the organization in the change process so that internal resistance can be minimized and organizational goals can be optimally achieved.